Konformizm polityczny Benjamina Franklina w latach 1764-1766 - Daszynska, Jolanta (Acta Universitatis Lodziensis. Folia Historica, 1999)
Benjamin Franklin as an agent of Pensylvania came back to England in 1764 (his first mission there was during the years 1757-1762). But it was the quite different country after the end of the Seven Years War. The war debts and other financial troubles pushed England to seek new sources of getting money. Following the advices of Lord Grenville, the Parliament imposed new taxes upon the American colonies. Those duties known as the Sugar Act and the Stamp Act involved great discontents in America. For the first time the taxes were put as general and the Parliament stood as a supreme legislature power for all the Empire. Franklin, opposite to the other colonial agents, did not see any wrong in such taxes. According to the Grenville’s suggestion, that the Americans can get the stamp money by themselves, he pointed out his friend John Hughes as a stamp collector. He also encouraged his friends to pay the taxes. He did not or he did not want to see the growing colonial resistance towards the Stamp Act. Franklin did not want to estrange the British politics from him, because he planned the change of government in Pennsylvania from the private to the royal one. Such was the aim of his mission. That might be also the reason why he supported the tax. The public opinion both in colonies and in England was against the Stamp Act. The British merchants started to loose their economic position and the income from the tax was less than it was planned before it came into live. The colonies protested against that measure. Those, who supported it were personally attacked, their houses were damaged (including the Franklin’s new house). They were accused to betray the interest of the colonies. Sometimes they were even killed. The colonial leaders gathered in so called Stamp Act Congress (Oct.7.1765) stated that Parliament has no right to tax the colonies because they had their own representative bodies. James Otis cried: „no taxation without the representation”. As a result, the Stamp Act Congress sent the resolution to the King to repeal the Stamp Act. The nonimportant agreement was announced as well. So, after the pressue of public opinion, B. Franklin very slowly had started to change his attitude towards that tax. Although he did not accept the decision of the Congress he wished the measure to be postponed for a year. He also suggested, that the only solution was the wisdom of the leaders, but not a strength. In late autumn of 1765 Franklin’s articles to the English press, though not signed by his name, showed the conflict from the American point of view. Franklin started to defend the Americans in their efforts to repeal the Stamp Act. However he constantly maintained the firm loyality to the Crown. From the begining of 1766 Franklin’s articles were more radical. He thought the Stamp Act as the most grevious and oppresive tax ever imposed. He also neglected the rights of the British Parliament to tax the colonies. Such opinions he presented during the examination before the Committee of the Whole of the House of Commons, Feb.13. He defended the colonial rights and neglected the supreme authority of Parliament all over the colonies. The examination was published both in England and in America, it was also translated into many languages. After that Franklin regained his lost reputation and was known as a hero, who’s great efforts made the Stamp Act repealed.